[Composite photograph of the view of campus from Poly P] (1940)
A view looking over the campus towards town and Bishop Peak. Red brick Dorms, North Mountain Dorms, and Administration Building are visible. This is a composite photograph of two individual slides with the identifiers ua-sel_00000287 and ua-sel_00000288.